Analysis of Internal Factors influencing Mudharabah Financing at Bank Mega Syariah for the Period 2016-2023 - Mutawali, Mutawali; Mukhoyyaroh, Mukhoyyaroh (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study aims to analyze the internal factors that affect Mudharabah financing for the period 2016-2023, both partially and simultaneously. This factor consists of FDR, CAR, NPF, and ROA. The research method of this research is quantitative descriptive. The type of sample used is purposive sampling, where the quarterly financial statements of the balance sheet and profit and loss at Bank Mega Syariah are sampled during the period 2016-2023. The study used secondary data in the form of financial reports of Bank Mega Syariah for the period 2016-2023, the internet, and journals. This study uses multiple linear regression analysis techniques with tools in the form of SPSS. The stages in this study consist of several tests, namely the classical assumption test, t-test, and F-test. the next stage is the Correlation Coefficient and Determination test. This research concludes that, partially, there is a negative influence of FDR and CAR on Mudharabah financing, and there is no influence of NPF and ROA on Mudharabah financing. Simultaneously, there is an influence of FDR, CAR, NPF, and ROA on Mudharabah financing. Keywords: FDR; CAR; NPF; ROA; Mudharabah Financing